Factors involved in nurses' responses to burnout: a grounded theory study - Nikravesh Mansoure; Oskouie Fatemeh; Rafii Forough (BMC, 2004)
Abstract Background Intense and long-standing problems in burn centers in Tehran have led nurses to burnout. This phenomenon has provoked serious responses and has put the nurses, patients and the organization under pressure. The challenge for managers and nurse executives is to understand the factors which would reduce or increase the nurses' responses to burnout and develop delivery systems that promote positive adaptation and facilitate quality care. This study, as a part of more extensive research, aims to explore and describe the nurses' perceptions of the factors affecting their responses to burnout. Methods Grounded theory was used as the method. Thirty- eight participants were recruited. Data were generated by unstructured interviews and 21 sessions of participant observations. Constant comparison was used for data analysis. Results Nurses' and patients' personal characteristics and social support influenced nurses' responses to burnout. Personal characteristics of the nurses and patients, especially when interacting, had a more powerful effect. They altered emotional, attitudinal, behavioral and organizational responses to burnout and determined the kind of caring behavior. Social support had a palliative effect and altered emotional responses and some aspects of attitudinal responses. Conclusions The powerful effect of positive personal characteristics and its sensitivity to long standing and intense organizational pressures suggests approaches to executing stress reduction programs and refreshing the nurses' morale by giving more importance to ethical aspects of caring. Moreover, regarding palliative effect of social support and its importance for the nurses' wellbeing, nurse executives are responsible for promoting a work environment that supports nurses and motivates them.